Karakteristik Morfometrik Kerbau Jantan Dengan Umur Yang Berbeda Di Pasar Ternak Kudus - fiqy hilmawan; Henny Nuraini; Rudy Priyanto (Universitas Islam Kadiri, 2019)
The aim of this research was to analyze body measurements (quantitative characteristics) of male buffalo in different ages in Pasar Ternak Kudus. This research used 24 heads of I0 male buffaloes, 26 heads of I1 male buffaloes, and 24 heads of I2 male buffaloes. Research method was survey and measuring body performances of male buffalo in body length, body height, hip height, chest deep and chest girt. Data obtained on this research were analyzed using t-test. The result of this research shown that the different ages gave significant different in all body performances of buffalo (P<0,05). It caused the buffalo still on the good growth phase in that age range. The body measurement of buffalo could be references for knowing the buffalo body condition according to animal breeder standardization of buffalo. Key words : male buffalo, body measurement, body length, body height, hip height, chest deep, chest girt.